2002
DOI: 10.1073/pnas.072087699
|View full text |Cite
|
Sign up to set email alerts
|

GCR1 , the putative Arabidopsis G protein-coupled receptor gene is cell cycle-regulated, and its overexpression abolishes seed dormancy and shortens time to flowering

Abstract: Although signaling through heterotrimeric G proteins has been extensively studied in eukaryotes, there is little information about this important signaling pathway in plants. We observed that expression of GCR1, the gene encoding the only known (but still putative) G protein-coupled receptor of Arabidopsis thaliana, is modulated during the cell cycle and during plant development. Overexpression of GCR1 in tobacco (Nicotiana tabacum) BY-2 cells caused an increase in thymidine incorporation and in the mitotic in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
66
1
2

Year Published

2003
2003
2018
2018

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(74 citation statements)
references
References 44 publications
5
66
1
2
Order By: Relevance
“…No additional vegetative phenotypes were observed in gcr1 gpa1, agb1 gcr1, and agb1 gcr1 gpa1 mutants. Colucci et al (2002) showed that plants ectopically expressing GCR1 flower early providing a clear prediction that plants lacking a functional GCR1 would flower late. However, gcr1 null mutants typically do not flower later than wild-type plants, and, under certain conditions, actually flower slightly, but statistically earlier, than wild-type plants (data not shown).…”
Section: And B)mentioning
confidence: 99%
See 2 more Smart Citations
“…No additional vegetative phenotypes were observed in gcr1 gpa1, agb1 gcr1, and agb1 gcr1 gpa1 mutants. Colucci et al (2002) showed that plants ectopically expressing GCR1 flower early providing a clear prediction that plants lacking a functional GCR1 would flower late. However, gcr1 null mutants typically do not flower later than wild-type plants, and, under certain conditions, actually flower slightly, but statistically earlier, than wild-type plants (data not shown).…”
Section: And B)mentioning
confidence: 99%
“…Although a ligand for GCR1 has not been identified, there is biochemical evidence that GCR1 does physically interact with GPA1 (Pandey and Assmann, 2004). Colucci et al (2002) reported that one of the phenotypes caused by overexpression of GCR1 in Arabidopsis is loss of seed dormancy. Expression of a germination marker, a phosphatase PP2A subunit, correlated with GCR1 overexpression (Colucci et al, 2002).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These cAMP receptors are not clustered with the Rhodopsin-like family, but GCR1 possesses a motif similar to the D-R-Y triplet (H-R-T). On the basis of transgenic studies Colucci et al (2002) recently suggested that GCR1 may be the gibberellic acid receptor.…”
Section: Putative Cor413 Functionmentioning
confidence: 99%
“…In contrast to animals, where they may number in the hundreds, plant G-protein subunits are coded by only one or sometimes two genes (Ma et al, 1990;Marsh and Kaufman, 1999;Assmann, 2002). Analysis of Arabidopsis plants mutant in GPA1 gene reveal that G proteins are likely to be involved in a number of processes critical for proper plant development, including hypocotyls and leaf formation , stomatal opening (Wang et al, 2001), abscisic acid (ABA) responsiveness/germination (Colucci et al, 2002;Ullah et al, 2002;Lapik and Kaufman, 2003), and both ABA and BL regulation of gene expression (K.M. Warpeha, unpublished data).…”
mentioning
confidence: 99%